2013
DOI: 10.1103/physreve.88.022137
|View full text |Cite
|
Sign up to set email alerts
|

From local force-flux relationships to internal dissipations and their impact on heat engine performance: The illustrative case of a thermoelectric generator

Abstract: We present an in-depth analysis of the sometimes understated role of the principle of energy conservation in linear irreversible thermodynamics. Our case study is that of a thermoelectric generator (TEG), which is a heat engine of choice in irreversible thermodynamics, owing to the coupling between the electrical and heat fluxes. We show why Onsager's reciprocal relations must be considered locally and how internal dissipative processes emerge from the extension of these relations to a global scale: The linear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 42 publications
(91 reference statements)
0
44
0
Order By: Relevance
“…Our results may helpful to design and operate a real thermoelectric device with broken timereversal symmetry for a productive outcome. Apertet et al studied an autonomous thermoelectric generator by extending the local Onsager relations to a global scale and showed that it naturally includes the Joule heat dissipation in input and output heat fluxes [70], which we will consider in our future study. The present study can also be extended to a thermoelectric heat devices beyond the linear response regime.…”
Section: Resultsmentioning
confidence: 99%
“…Our results may helpful to design and operate a real thermoelectric device with broken timereversal symmetry for a productive outcome. Apertet et al studied an autonomous thermoelectric generator by extending the local Onsager relations to a global scale and showed that it naturally includes the Joule heat dissipation in input and output heat fluxes [70], which we will consider in our future study. The present study can also be extended to a thermoelectric heat devices beyond the linear response regime.…”
Section: Resultsmentioning
confidence: 99%
“…However, under the same conditions, the linear thermoelectric coefficient can exhibit B asymmetries if carriers experience inelastic scattering inside the conductor [26][27][28][29] 6 . As a consequence, the two-terminal thermopower need not be an even function of B and its degree of asymmetry determines the thermodynamic efficiency of a system with broken timereversal symmetry [30][31][32][33]. The asymmetries we discuss here survive in the purely elastic case and appear only in the nonlinear regime of transport.…”
Section: Introductionmentioning
confidence: 92%
“…1). Then, based on Onsager formalism and Domenicali's heat equation [42,43], thermal fluxes at the end points of TEM are written as follows.…”
Section: Teg Modelmentioning
confidence: 99%